Adaptasi Pendidikan Pesantren: Memperkuat Hard Skill di Pondok Pesantren Al Hikmah 02 Brebes - bustomi, ahmad; Ahmad Bustomi; Isti Fatonah (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2024)
Pesantren will be irrelevant if they do not adapt to people need and market world. It is ideally provide life skill for students as a form of adjusment. The aim of this research is to analyze the adaptation and transformation in Pesantren as education institution spesifically as a action to facilitate students in a form of hard skill learning. The research method utilized by researcher was qualitative through interview, observation and documentation. The research results emerge that there are several aspects into pesantren adaptation such as adaptation in human resource, formal legality, curriculum, addition time of learning, learning facilities, and learning method.